2012
DOI: 10.26719/2012.18.8.827
|View full text |Cite
|
Sign up to set email alerts
|

Problems and perceived needs for medical ethics education of resident physicians in Alexandria teaching hospitals, Egypt

Abstract: There is a call for greater preparation for the ethical challenges encountered by physicians in their future professional duties. This study in Egypt aimed to reveal problems and perceived needs for medical ethics education of resident physicians working at University of Alexandria hospitals. In a descriptive, cross-sectional survey, 128 residents answered a self-administered questionnaire. More than half were of the opinion that their medical ethics course was ineffective; 56.3% mentioned poor curricular plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The characteristics of the 128 resident physicians who completed the questionnaires have been described in a previous paper [3]. Two-fifths of residents (40.6%) had learned about medical ethics from their own experience at work, 27.3% had read about it and 18.0% had their knowledge from their medical education; only 14.1% gained their knowledge from exposure to a training course on the subject.…”
Section: Physicians' Characteristicsmentioning
confidence: 99%
“…The characteristics of the 128 resident physicians who completed the questionnaires have been described in a previous paper [3]. Two-fifths of residents (40.6%) had learned about medical ethics from their own experience at work, 27.3% had read about it and 18.0% had their knowledge from their medical education; only 14.1% gained their knowledge from exposure to a training course on the subject.…”
Section: Physicians' Characteristicsmentioning
confidence: 99%
“…A literature review of needs assessment models and methods of data collection for needs assessments in general and specifically in medical ethics education (10,(16)(17)(18)(19)(20) informed the design and content of the RGNs survey. Two neonatologists with expertise in teaching ethics and communication and one senior NPM trainee drafted the first version.…”
Section: National Survey Of Recent Graduates Of Npm Training and Npm Training Pdsmentioning
confidence: 99%
“…Some evidence indicated that dental residents had lower level of knowledge of ethics and professionalism than their peers in medical specialties 5 . Residents face unique ethical conflicts due to their multiple responsibilities 6 and need to be prepared for such encounters. On the other hand, the opportunities for formal ethics education decline significantly during the residency programs 7 .…”
Section: Introductionmentioning
confidence: 99%